The use of micro computed tomography to ascertain the morphology of bloodstains on fabric - Dicken, Lisa; Knock, Clare; Beckett, Sophie; de Castro, Therese C.; Nickson, Tania; Carr, Debra J. (Elsevier, 2015)
Very little is known about the interactions of blood and fabric and how bloodstains on fabric are formed. Whereas the blood stain size for non-absorbent surfaces depends on impact velocity, previous work has suggested that for fabrics the blood stain size is independent of impact velocity when the drop size is kept constant. Therefore, a greater understanding of the interaction of blood and fabric is required. This paper explores the possibility of using a micro computed tomography (CT) scanner to study bloodstain size and shape throughout fabrics. Two different fabrics were used: 100% cotton rib knit and 100% cotton bull drill. Bloodstains were created by dropping blood droplets from three heights; 500 mm, 1000 mm and 1500 mm. Results from the CT scanner clearly showed the bloodstain shape throughout the fabric. The blood was found to form a diamond shaped stain, with the maximum cross-sectional area 0.3–0.5 mm below the surface. The bloodstain morphology depended on both the impact velocity and fabric structure.
Keywords: Wicking; Wetting; Absorbent surfaces